Aluminum-magnesium-silicon alloy monofilament and preparation method thereof
By adding erbium, lanthanum (cerium), and boron elements to the aluminum-magnesium-silicon alloy wires and adopting a specific preparation process, the problem of low conductivity of existing aluminum-magnesium-silicon alloy wires is solved, and aluminium alloy monofilaments with high conductivity and high tensile strength is achieved, meeting the needs of efficient electrical energy transmission.
Patent Information
- Application Number
- CN202010504114.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-06-05
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-06-05
AI Technical Summary
The existing aluminum-magnesium-silicon alloy wires have low conductivity and are difficult to meet the transmission requirements of energy saving and loss reduction.
By using electrical aluminum ingots with a purity of 99.7% as raw material, trace amounts of erbium, lanthanum (cerium), and boron elements were added, and specific preparation processes were adopted, including smelting, standing decomposition, nitrogen blowing, casting, rolling, wire drawing and other steps, aluminum alloy monofilaments with conductivity ≥56% IACS (20℃), tensile strength ≥300MPa, and elongation ≥3.0%.
It achieves a combination of high conductivity and high tensile strength, meets the needs of efficient power transmission, and reduces transmission losses.
Abstract
Description
Technical Field
[0001] The invention relates to an electrical conductor material, in particular to an aluminum alloy monofilament. Background Art
[0002] With the rapid development of industry, the demand for electricity is rising year by year. As an important carrier of power transmission in power grids, the comprehensive performance of overhead wires directly affects the safety of power transmission and the efficiency of energy transmission. High-strength overhead wires can not only ensure the safety of wire operation in harsh service environments such as icing and wind loads, but also their high conductivity can improve the power transmission efficiency of transmission lines and reduce transmission losses.
[0003] Aluminum-magnesium-silicon alloys are the preferred materials for long-distance and large-span transmission lines due to their low alloying degree, high specific strength, good mechanical and electrical conductivity, and high corrosion resistance. However, the existing aluminum-magnesium-silicon alloy conductors have low electrical conductivity and are difficult to meet the transmission requirements of energy saving and loss reduction.
[0004] Therefore, it is necessary to provide an aluminum-magnesium-silicon alloy wire material with high strength and high conductivity. Summary of the invention
[0005] The purpose of the present invention is to prepare a high-strength and high-conductivity aluminum-magnesium-silicon alloy monofilament material using electrical aluminum ingots with a purity of 99.7% as raw material to meet the needs of the prior art.
[0006] The present invention improves the alloy microstructure and comprehensive performance by adding trace erbium, lanthanum (cerium), boron elements and corresponding preparation technology, and obtains aluminum alloy monofilament with conductivity ≥56%IACS (20°C), tensile strength ≥300MPa, and elongation ≥3.0%.
[0007] The technical solution for implementing the above purpose is as follows:
[0008] An aluminum-magnesium-silicon alloy monofilament, the improvement of which lies in that the alloy monofilament comprises the following components by mass percentage:
[0009] Magnesium: 0.50-0.70%, silicon: 0.30-0.50%, erbium: 0.30-0.50%, lanthanum (cerium): 0-0.08%, boron: 0.01-0.02%, impurity elements vanadium + titanium + chromium + manganese ≤ 0.01%, and the rest are aluminum and unavoidable impurities.
[0010] Among them, erbium is 0.30-0.50%, lanthanum (cerium) is 0-0.08%, and boron is 0.01-0.02%.
[0011] The monofilament preparation process includes: melting an aluminum ingot having a purity higher than a preset purity threshold in a melting furnace at 730-750° C.;
[0012] Adding aluminum-lanthanum master alloy, aluminum-cerium master alloy or lanthanum-cerium mixed rare earth to the obtained melt at 730-740° C., and adding aluminum-boron master alloy, and letting it stand for the first time to remove impurities after melting;
[0013] Adding pure magnesium, aluminum-silicon master alloy and aluminum-erbium master alloy to the molten liquid after standing and removing impurities at 730-750°C, melting and stirring, and then standing for a second time to remove impurities;
[0014] Blow nitrogen gas at a pressure of 0.5-0.8 MPa into the melt at 710-730°C, let it stand for a third time and skim off the slag;
[0015] Pour the molten metal at 700-720°C into a metal mold to obtain an ingot;
[0016] The ingot is kept at 510-530°C for 1-2 hours, rolled or extruded into a φ9.5mm rod, water quenched and drawn.
[0017] The ingot rolling is continuous casting and rolling, which includes subjecting the molten metal obtained by slagging to a rolling temperature of 510-530°C, a final rolling temperature of not less than 400°C, cooling with a coolant, and producing a rod at 90-100°C to obtain a rod material.
[0018] The extrusion comprises extruding the ingot obtained by casting the molten metal after slagging at a temperature of 510-530°C, extruding at a temperature not lower than 400°C, cooling with a coolant, and producing a rod at 90-100°C to obtain a rod material.
[0019] The rod material is drawn through 8 to 12 passes to obtain φ3 to 4 mm single wires; and the single wires are aged at 175 to 190° C. for 6 to 10 hours to obtain aluminum-magnesium-silicon alloy single wires.
[0020] The first period of standing to remove impurities includes: standing for 40 to 60 minutes, pouring 4 / 5 of the solution from the upper part of the smelting furnace into another insulation furnace to obtain a solution for standing to remove impurities.
[0021] Wherein, the second time is 15 to 20 minutes; the third time is 20 to 30 minutes.
[0022] The stirring time and the nitrogen blowing time are both 10 to 15 minutes.
[0023] Among them, the aluminum ingots with a purity higher than a preset purity threshold are melted in a melting furnace at 730-750°C;
[0024] Adding aluminum-lanthanum master alloy, aluminum-cerium master alloy or lanthanum-cerium mixed rare earth to the obtained melt at 730-740° C., and adding aluminum-boron master alloy, and letting it stand for the first time to remove impurities after melting;
[0025] Adding pure magnesium, aluminum-silicon master alloy and aluminum-erbium master alloy to the molten liquid after standing and removing impurities at 730-750°C, melting and stirring, and then standing for a second time to remove impurities;
[0026] Blow nitrogen gas at a pressure of 0.5-0.8 MPa into the melt at 710-730°C, let it stand for a third time and skim off the slag;
[0027] Pour the molten metal at 700-720°C into a metal mold to obtain an ingot;
[0028] The ingot is kept at 510-530℃ for 1-2h and rolled or extruded into The rod is water quenched and drawn to obtain an aluminum-magnesium-silicon alloy monofilament with the following composition: magnesium: 0.50-0.70%, silicon: 0.30-0.50%, erbium: 0.30-0.50%, lanthanum (cerium): 0-0.08%, boron: 0.01-0.02%, impurity elements vanadium + titanium + chromium + manganese ≤0.01%, and the rest are aluminum and unavoidable impurities.
[0029] Compared with the closest prior art, the technical solution provided by the present invention has the following beneficial effects:
[0030] The magnesium in the technical solution provided by the present invention has a significant strengthening effect on aluminum. For every 1% increase in magnesium, the tensile strength of the obtained product increases by about 34MPa. In the aluminum-magnesium-silicon alloy, the strengthening phase magnesium silicide plays a strengthening role on the alloy; and the magnesium silicide strengthening phase also has a certain influence on the electrical conductivity of the alloy. When the magnesium content is low, the conductivity of the alloy is generally high and the strength is low, but a moderate excess of magnesium can fully precipitate the magnesium silicide after heat treatment, which is also beneficial to the improvement of the electrical conductivity of the alloy.
[0031] Silicon in the technical solution of the present invention, which is one of the most common elements in aluminum alloys, can form some compounds in the alloy, so that the aluminum alloy can be heat-treated, the castability and welding fluidity of the aluminum alloy can be improved, and the aluminum alloy has higher mechanical properties.
[0032] The rare earth element erbium can significantly improve the strength of aluminum alloys. In addition, the addition of erbium can also reduce the dendrite segregation of aluminum alloys and significantly refine the grain structure of the alloy. The technical solution provided by the present invention notes that the grain refinement mechanism of erbium is related to its addition amount. When the erbium content is low, it conforms to the traditional rare earth refinement mechanism. When the erbium content is high, due to the formation of primary aluminum 3 erbium particles in the melt, it can serve as a heterogeneous nucleation core during crystallization nucleation, thereby significantly refining the grain structure; in addition, erbium can also react with some impurity elements in the aluminum alloy, transforming the impurity elements from the atomic state to the precipitated state, thereby improving the conductivity of the aluminum alloy.
[0033] The rare earth selected from lanthanum, cerium or lanthanum-cerium mixed rare earth in the technical solution of the present invention has the function of purifying alloy liquid, changing impurity elements such as iron and silicon from solid solution atoms into the second phase, reducing lattice distortion and improving the conductivity of aluminum alloy.
[0034] The boron in the technical solution of the present invention can react with transition group components such as chromium, manganese, vanadium and titanium as impurity elements, so that they are transformed from a solid solution state to a combined state and deposited at the bottom of the melt, thereby improving the electrical conductivity of the aluminum alloy. The boronization treatment provided by the present invention is an effective method for reducing impurities in aluminum alloys.
[0035] Furthermore, the vanadium, manganese, chromium, and titanium in the technical solution of the present invention are all impurity elements in aluminum alloys, which have a great influence on the electrical conductivity of aluminum alloys. When impurity elements such as titanium, vanadium, manganese, and chromium exist in the aluminum alloy conductor in a solid solution state, they can easily absorb free electrons in the conductor material and fill their incomplete electron layers, which reduces the number of conduction electrons and leads to a decrease in the electrical conductivity of the aluminum alloy conductor. It was found that for every 1% increase in the content of (chromium + titanium + manganese + vanadium), the harmful effect on the electrical conductivity of aluminum is equivalent to 5 times that of every 1% increase in silicon. The technical solution of the present invention plays an important role in ensuring the quality of aluminum conductors by strictly controlling the content of these elements.
[0036] The technical solution provided by the present invention adds rare earth elements erbium, lanthanum (cerium) and boron to the aluminum-magnesium-silicon alloy, and adopts a corresponding aging treatment process to make some impurity atoms generate a second phase and remove it through precipitation, and then adopts a corresponding aging treatment to precipitate the melt atoms, which not only plays a strengthening role, but also reduces the lattice distortion, thereby improving the electrical conductivity, thereby obtaining an aluminum alloy monofilament with a conductivity of ≥56% IACS (20°C), a tensile strength of ≥300MPa, and an elongation of ≥3.0%. Specific implementation plan
[0037] The technical solution provided by the present invention is described in detail below by way of specific embodiments.
[0038] The “from the upper part of the melting furnace” herein means taking the molten metal from the “upper part of the melting furnace” out to another holding furnace.
[0039] The conductivity of each embodiment of the present application is tested in accordance with the requirements of GB / T 23308 Aluminum-magnesium-silicon alloy round wire for overhead stranded cables, and the conductivity is converted from the single-wire resistance measured by a TEGAM 1750 high-precision, high-speed programmable micro-ohmmeter; the tensile strength is measured using a Sansi CMT6104 microcomputer-controlled electronic universal testing machine.
[0040] Example 1
[0041] An aluminum-magnesium-silicon alloy monofilament, wherein the components and their mass percentages are:
[0042] element magnesium silicon erbium Lanthanum (Cerium) boron Vanadium + Titanium + Chromium + Manganese aluminum Mass fraction / wt.% 0.50 0.30 0.50 0.08 0.01 0.01 margin
[0043] The electrical pure aluminum ingot with a purity of 99.7% is added into a melting furnace at 730°C for melting;
[0044] After melting, add aluminum-lanthanum master alloy and aluminum-boron master alloy at 740°C, stir thoroughly after complete melting, and let stand for 40 minutes;
[0045] Pour 4 / 5 of the melt from the top of the melting furnace into another holding furnace, add pure magnesium, aluminum-silicon master alloy, and aluminum-erbium master alloy at 730°C, stir for 15 minutes after complete melting, and let stand for 15 minutes;
[0046] Blow in 0.5-0.8MPa nitrogen at 715℃ for 15min, let stand for 20min and then skim off the slag;
[0047] Pour the aluminum alloy liquid at 700°C into the metal mold to obtain an ingot of 22×22×200mm;
[0048] The ingot kept at 510℃ for 2h was rolled into φ9.5mm aluminum alloy round rod, then quickly water quenched, and after 8 drawing passes, φ4mm aluminum alloy single wire was obtained, which was then kept at 175℃ for 10h to obtain aluminum-magnesium-silicon alloy single wire. The conductivity of the single wire was 56.2% IACS (20℃), the tensile strength was 307MPa, and the elongation was 3.2%.
[0049] Example 2
[0050] An aluminum-magnesium-silicon alloy monofilament, the mass percentage of each component of which is:
[0051] element magnesium silicon erbium Lanthanum (Cerium) boron Vanadium + Titanium + Chromium + Manganese aluminum Mass fraction / wt.% 0.70 0.50 0.40 0.05 0.015 0.008 margin
[0052] Electrically pure aluminum ingots with a purity of 99.7% are added to the melting furnace at a melting temperature of 750°C; after the pure aluminum is completely melted, aluminum-cerium master alloy and aluminum-boron master alloy are added at 730°C, fully stirred after complete melting, and left to stand for 50 minutes; 4 / 5 of the upper aluminum liquid in the melting furnace is poured into another insulation furnace, pure magnesium, aluminum-silicon master alloy, and aluminum-erbium master alloy are added at 750°C, stirred for 10 minutes after complete melting, and left to stand for 20 minutes. Their final contents are as shown above. At 720°C, 0.5-0.8MPa nitrogen is blown in for 10 minutes, and the slag is removed after standing for 30 minutes. At 710°C, the aluminum alloy liquid is poured into a metal mold to obtain an ingot of 22×22×200mm. The ingot is kept at 520°C for 1.5 hours, rolled into a φ9.5mm aluminum alloy round rod, and then quickly water quenched. After 10 drawing passes, a φ3.5 mm aluminum alloy single wire was obtained and then kept at 185°C for 8 hours. The conductivity of the single wire was 56% IACS (20°C), the tensile strength was 311 MPa, and the elongation was 3.0%.
[0053] Example 3
[0054] An aluminum-magnesium-silicon alloy monofilament, the mass percentage of each component of which is:
[0055] element magnesium silicon erbium Lanthanum (Cerium) boron Vanadium + Titanium + Chromium + Manganese aluminum Mass fraction / wt.% 0.60 0.40 0.30 0.04 0.02 0.007 margin
[0056] Electrically pure aluminum ingots with a purity of 99.7% are added to the smelting furnace at a smelting temperature of 740°C; after the pure aluminum is completely melted, lanthanum-cerium mixed rare earth and aluminum-boron master alloy are added at 735°C, fully stirred after complete melting, and left to stand for 50 minutes; 4 / 5 of the upper aluminum liquid in the smelting furnace is poured into another insulation furnace, pure magnesium, aluminum-silicon master alloy, and aluminum-erbium master alloy are added at 740°C, stirred for 15 minutes after complete melting, and left to stand for 20 minutes. Their final contents are as shown above. At 730°C, 0.5-0.8MPa nitrogen is blown in for 15 minutes, and the slag is removed after standing for 25 minutes. At 720°C, the aluminum alloy liquid is poured into a metal mold to obtain an ingot of 22×22×200mm. The ingot is kept at 530°C for 1 hour, rolled into a φ9.5mm aluminum alloy round rod, and then quickly water quenched. After 12 drawing passes, a φ3.0 mm aluminum alloy single wire was obtained and then kept at 190°C for 6 hours. The conductivity of the single wire was 56.1% IACS (20°C), the tensile strength was 308 MPa, and the elongation was 3.2%.
[0057] Example 4
[0058] An aluminum-magnesium-silicon alloy monofilament, the components and their weight percentages are:
[0059] element magnesium silicon erbium Lanthanum (Cerium) boron Vanadium + Titanium + Chromium + Manganese aluminum Mass fraction / wt.% 0.65 0.35 0.35 0.02 0.02 0.006 margin
[0060] Electrically pure aluminum ingots with a purity of 99.7% are added to the smelting furnace at a smelting temperature of 740°C; after the pure aluminum is completely melted, lanthanum-cerium mixed rare earth and aluminum-boron master alloy are added at 735°C, fully stirred after complete melting, and left to stand for 50 minutes; 4 / 5 of the upper aluminum liquid in the smelting furnace is poured into another insulation furnace, pure magnesium, aluminum-silicon master alloy, and aluminum-erbium master alloy are added at 740°C, stirred for 15 minutes after complete melting, and left to stand for 20 minutes. Their final contents are as shown above. At 730°C, nitrogen gas with a pressure of 0.5-0.8MPa is blown in for 15 minutes, and the slag is removed after standing for 25 minutes. At 720°C, the aluminum alloy liquid is poured into a metal mold to obtain an ingot of 22×22×200mm. The ingot is kept at 530°C for 1h, rolled into a φ9.5mm aluminum alloy round rod, and then quickly water quenched. After 11 drawing passes, a φ3.2 mm aluminum alloy single wire was obtained and then kept at 180°C for 9 hours. The conductivity of the single wire was 56.2% IACS (20°C), the tensile strength was 305 MPa, and the elongation was 3.1%.
[0061] Example 5
[0062] An aluminum-magnesium-silicon alloy monofilament, the components and their weight percentages are:
[0063]
[0064]
[0065] Electrically pure aluminum ingots with a purity of 99.7% are added to the smelting furnace at a smelting temperature of 750°C; after the pure aluminum is completely melted, aluminum-lanthanum master alloy and aluminum-boron master alloy are added at 740°C, fully stirred after complete melting, and allowed to stand for 45 minutes; 4 / 5 of the upper aluminum liquid in the smelting furnace is poured into another insulation furnace, pure magnesium, aluminum-silicon master alloy, and aluminum-erbium master alloy are added at 750°C, stirred for 15 minutes after complete melting, and allowed to stand for 15 minutes, so that their final contents are as shown above. At 20°C, nitrogen gas with a pressure of 0.5-0.8MPa is blown in for 10 minutes, and the slag is removed after standing for 30 minutes. The aluminum alloy liquid is poured into a metal mold at 710°C to obtain an ingot of 22×22×200mm. The ingot is kept at 515°C for 2h, rolled into a φ9.5mm aluminum alloy round rod, and then quickly water quenched. After 9 drawing passes, the φ3.7 mm aluminum alloy single wire was obtained and then kept at 185°C for 8 hours. The conductivity of the single wire was 56.1% IACS (20°C), the tensile strength was 301 MPa, and the elongation was 3.3%.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
[0067] Those skilled in the art will appreciate that the embodiments of the present application may be provided as methods, systems, or computer program products. Therefore, the present application may adopt the form of a complete hardware embodiment, a complete software embodiment, or an embodiment in combination with software and hardware. Moreover, the present application may adopt the form of a computer program product implemented in one or more computer-usable storage media (including but not limited to disk storage, CD-ROM, optical storage, etc.) that include computer-usable program code.
[0068] The present application is described with reference to the flowchart and / or block diagram of the method, device (system) and computer program product according to the embodiment of the present application. It should be understood that each process and / or box in the flowchart and / or block diagram, and the combination of the process and / or box in the flowchart and / or block diagram can be realized by computer program instructions. These computer program instructions can be provided to a processor of a general-purpose computer, a special-purpose computer, an embedded processor or other programmable data processing device to produce a machine, so that the instructions executed by the processor of the computer or other programmable data processing device produce a device for realizing the function specified in one process or multiple processes in the flowchart and / or one box or multiple boxes in the block diagram.
[0069] These computer program instructions may also be stored in a computer-readable memory that can direct a computer or other programmable data processing device to work in a specific manner, so that the instructions stored in the computer-readable memory produce a manufactured product including an instruction device that implements the functions specified in one or more processes in the flowchart and / or one or more boxes in the block diagram.
[0070] These computer program instructions can also be loaded onto a computer or other programmable data processing device, so that a series of operation steps are executed on the computer or other programmable device to produce a computer-implemented process, thereby executing on the computer or other programmable data processing device.
Claims
1. An aluminum-magnesium-silicon alloy monofilament, characterized in that: The alloy monofilament comprises the following components by mass percentage: Magnesium: 0.55~0.70%, silicon: 0.30~0.50%, erbium: 0.35~0.50%, lanthanum and / or cerium: 0~0.08%, boron: 0.01~0.02%, impurity elements vanadium + titanium + chromium + manganese ≤ 0.01%, the rest are aluminum and unavoidable impurities; During the smelting process, firstly, aluminum-lanthanum master alloy, aluminum-cerium master alloy or lanthanum-cerium mixed rare earth and aluminum-boron master alloy are added to the obtained melt at 730-740°C, and the melt is allowed to stand for a first time to remove impurities after melting; then, pure magnesium, aluminum-silicon master alloy and aluminum-erbium master alloy are added at 730-750°C, and the melt is melted, stirred and allowed to stand for a second time to remove impurities.
2. The aluminum-magnesium-silicon alloy monofilament according to claim 1, characterized in that: The preparation process of the monofilament comprises: Melt the aluminum ingots with a purity higher than the preset purity threshold in a melting furnace at 730-750°C; Adding aluminum-lanthanum master alloy, aluminum-cerium master alloy or lanthanum-cerium mixed rare earth to the obtained melt at 730-740° C., and adding aluminum-boron master alloy, and letting it stand for the first time to remove impurities after melting; Add pure magnesium, aluminum-silicon master alloy and aluminum-erbium master alloy to the molten liquid which has been left to stand for impurity removal at 730-750°C, melt and stir, and then leave it to stand for a second time for impurity removal; Blow nitrogen gas at a pressure of 0.5-0.8 MPa into the melt at 710-730°C, let it stand for a third time and remove the slag; Pour the molten metal at 700-720℃ into the metal mold to obtain an ingot; The ingot is kept at 510-530°C for 1-2 hours, rolled or extruded into a φ9.5mm rod, water quenched and drawn.
3. The aluminum-magnesium-silicon alloy monofilament according to claim 2, characterized in that: The ingot rolling is continuous casting and rolling, which includes subjecting the molten metal obtained by slagging to a rolling temperature of 510-530°C, a final rolling temperature of not less than 400°C, cooling with a coolant, and producing a rod at 90-100°C to obtain a rod material.
4. The aluminum-magnesium-silicon alloy monofilament according to claim 2, characterized in that: The extrusion comprises the following steps: extruding the ingot obtained by casting the molten metal after slagging at a temperature of 510-530° C., extruding at a temperature not lower than 400° C., cooling with a coolant, and producing a rod at a temperature of 90-100° C. to obtain a rod material.
5. An aluminum-magnesium-silicon alloy monofilament according to claim 3 or 4, characterized in that: Drawing the rod material through 8 to 12 passes to obtain a φ3 to 4 mm monofilament; and The single wire is aged at 175-190°C for 6-10 hours to obtain an aluminum-magnesium-silicon alloy single wire.
6. The aluminum-magnesium-silicon alloy monofilament according to claim 2, characterized in that: The first period of standing still to remove impurities includes: standing still for 40 to 60 minutes, pouring 4 / 5 of the solution from the upper part of the smelting furnace into another insulation furnace to obtain a solution for standing still to remove impurities.
7. The aluminum-magnesium-silicon alloy monofilament according to claim 2, characterized in that: The second time is 15 to 20 minutes; the third time is 20 to 30 minutes.
8. The aluminum-magnesium-silicon alloy monofilament according to claim 2, characterized in that: The stirring time and the nitrogen blowing time are both 10~15min.
9. A method for preparing aluminum-magnesium-silicon alloy monofilament, characterized in that: include: Melt the aluminum ingots with a purity higher than the preset purity threshold in a melting furnace at 730-750°C; Adding aluminum-lanthanum master alloy, aluminum-cerium master alloy or lanthanum-cerium mixed rare earth to the obtained melt at 730-740° C., and adding aluminum-boron master alloy, and letting it stand for the first time to remove impurities after melting; Add pure magnesium, aluminum-silicon master alloy and aluminum-erbium master alloy to the molten liquid which has been left to stand for impurity removal at 730-750°C, melt and stir, and then leave it to stand for a second time for impurity removal; Blow nitrogen gas at a pressure of 0.5-0.8 MPa into the melt at 710-730°C, let it stand for a third time and remove the slag; Pour the molten metal at 700-720℃ into the metal mold to obtain an ingot; The ingot, which is kept at 510-530°C for 1-2 hours, is rolled or extruded into a φ9.5mm rod, water quenched and drawn to obtain an aluminum-magnesium-silicon alloy monofilament with the following composition: magnesium: 0.55-0.70%, silicon: 0.30-0.50%, erbium: 0.35-0.50%, lanthanum and / or cerium: 0-0.08%, boron: 0.01-0.02%, impurity elements vanadium + titanium + chromium + manganese ≤ 0.01%, and the rest are aluminum and unavoidable impurities.
Citation Information
Patent Citations
Novel high-strength high-conductivity aluminium-alloy conductor and production method thereof
CN103498084A
Medium-strength high-conductivity aluminum alloy single wire and preparation method thereof
CN106834820A
Aluminum alloy and preparation method and application thereof
US20210207249A1